2013
DOI: 10.1021/jz400938q
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Neutral Versus Polyelectrolyte Behavior of Poly(ethylene glycol)s in Alkali Ion Solutions using Single-Nanopore Recording

Abstract: We examine the effect of alkali ions (Li + , Na + , K + , Rb + , Cs + ) on the partitioning of neutral and flexible poly(ethylene glycol) into the alpha-hemolysin (α-HL) nanopore for a large range of applied voltages at high salt concentration. The neutral polymer behaves as if charged, that is, the event frequency increases with applied voltage, and the residence times decrease with the electric force for all cations except Li + . In contrast, in the presence of LiCl, we find the classical partitioning behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 48 publications
10
72
0
Order By: Relevance
“…However, we may be at the limit of the model used to extrapolate the energy barrier for the translocation, being entry and transport processes, of proteins into the pore. We demonstrated that at low electrical driving force these unfolded proteins translocated through the aerolysin nanopore in a non-extended conformation, as previously observed for a neutral polymer, 71 according to the Daoud and de Gennes “blob” model. 76 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, we may be at the limit of the model used to extrapolate the energy barrier for the translocation, being entry and transport processes, of proteins into the pore. We demonstrated that at low electrical driving force these unfolded proteins translocated through the aerolysin nanopore in a non-extended conformation, as previously observed for a neutral polymer, 71 according to the Daoud and de Gennes “blob” model. 76 …”
Section: Discussionsupporting
confidence: 80%
“…70,71 Because the covalent dimer is twice the length of pertactin, we were able to extract experimentally the entropic barrier contribution for the entry of the proteins inside the pore: ΔUdimermonomer=kBTlntrue(ΠdimerΠmonomertrue) The partition coefficient Π reads Π = (1/ N A v pore )( Pr ), where N A is the Avogadro constant, v pore represents the pore volume, and the residence probability Pr = τ occup /( τ tot c ), where τ occup is the time occupied per protein inside the pore, τ tot is the total acquisition time and c is the protein concentration. 72 Thus, ΔU dimer → monomer = U entropic = k B T ln ( Pr dimer / Pr monomer ) = 0.73 ± 0.04 k B T , which is the estimated entropic contribution.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main features of the α -hemolysin nanopore is its stability over a wide range of experimental conditions, including aqueous solution of different salts2829 at widely different concentrations1630, denaturing agents3132, the variation of pH3334 or of temperature3536. In particular, single-channel currents through α -hemolysin have previously been recorded at temperature varying between 2 °C35 and 93 °C36.…”
Section: Resultsmentioning
confidence: 99%
“…GNPs prior to PEGylation are generally negatively charged, due to the use of citrate as stabilizing agent during synthesis, which is negatively charged (E. C. Cho et al 2009a). PEG, in contrast, is generally neutral (Breton et al 2013). Coating of GNPs with PEG has an insulating effect that lowers the zeta potential magnitude.…”
Section: Discussionmentioning
confidence: 99%